2004
DOI: 10.1038/sj.gt.3302325
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus expressing Fas ligand gene decreases airway hyper-responsiveness and eosinophilia in a murine model of asthma

Abstract: Allergic asthma is characterized by airway hyper-responsiveness (AHR) and cellular infiltration of the airway with predominantly eosinophils and Th2 cells. The normal resolution of inflammation in the lung occurs through the regulated removal of unneeded cells by Fas-Fas ligandmediated apoptosis. Fas ligand (FasL) is a member of the tumor necrosis factor family, and when bound to Fas, it induces apoptosis of the cells. To examine the effect of the FasL gene on airway inflammation and immune effector cells in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
1
15
0
2
Order By: Relevance
“…The whole-body plethysmography was measured with the Penh system (Penh ¼ pause  (peak expiratory box flow/peak inspiratory box flow)) as described previously. 35,36 Briefly, mice were placed in the main chamber of a whole-body plethysmography and challenged with aerosolized normal saline, and later challenged with increasing doses of MCh (6.25-50 mg ml À1 ; Sigma, St Louis, MO, USA). Results were expressed for each concentration of MCh as a percentage of the baseline Penh value after exposure to normal saline.…”
Section: Determination Of the Airway Functionmentioning
confidence: 99%
“…The whole-body plethysmography was measured with the Penh system (Penh ¼ pause  (peak expiratory box flow/peak inspiratory box flow)) as described previously. 35,36 Briefly, mice were placed in the main chamber of a whole-body plethysmography and challenged with aerosolized normal saline, and later challenged with increasing doses of MCh (6.25-50 mg ml À1 ; Sigma, St Louis, MO, USA). Results were expressed for each concentration of MCh as a percentage of the baseline Penh value after exposure to normal saline.…”
Section: Determination Of the Airway Functionmentioning
confidence: 99%
“…Fas ligand (FasL) is another target that mediates the apoptotic pathway in lymphocytes. Chuang et al delivered FasL intratracheally using an adenoviral vector and showed an attenuation of AHR and airway eosinophilia (due to an increase in eosinophil apoptosis), as well as a decrease in IL-5, IL-13, and eotaxin in BAL [122].…”
Section: Therapeutic Potential Of Dna Gene Therapy For Asthmamentioning
confidence: 97%
“…11 For systemic immunization, mice were sensitized by intraperitoneal injection of 50 mg of OVA (Sigma, St Louis, MO, USA) mixed with 4 mg of alum on day 0; they were then given 25 mg of OVA mixed with 4 mg of alum on days 14, 21 and 28. On days 42, 43 and 44, mice were challenged with 100 mg/ mouse (in a total volume of 40 ml) of OVA by intranasal administration.…”
Section: Immunization and As 2 O 3 Treatmentmentioning
confidence: 99%